Single-Walled Carbon Nanotubes as Fluorescence Biosensors for Pathogen Recognition in Water Systems. (19th June 2008) - Upadhyayula, Venkata K. K.; Ghoshroy, Soumitra; Nair, Vinod S.; Smith, Geoffrey B.; Mitchell, Martha C.; Deng, Shuguang
Abstract : The possibility of using single-walled carbon nanotubes (SWCNTs) aggregates as fluorescence sensors for pathogen recognition in drinking water treatment applications has been studied. Batch adsorption study is conducted to adsorb large concentrations of Staphylococcus aureus aureus SH 1000 and Escherichia coli pKV-11 on single-walled carbon nanotubes. Subsequently the immobilized bacteria are detected with confocal microscopy by coating the nanotubes with fluorescence emitting antibodies. The Freundlich adsorption equilibrium constant ( k ) for S.aureus and E.coli determined from batch adsorption study was found to be 9 × 10 8 and 2 × 10 8  ml/g, respectively. The visualization of bacterial cells adsorbed on fluorescently modified carbon nanotubes is also clearly seen. The results indicate that hydrophobic single-walled carbon nanotubes have excellent bacterial adsorption capacity and fluorescent detection capability. This is an important advancement in designing fluorescence biosensors for pathogen recognition in water systems.